Intrusion detection using ant colony approach in wireless sensor networks - Agarkhed, Jayashree; Kalnoor, Gauri (International Journal of Engineering and Technology, 2018)
Design of an intrusion detection system in the sensor network to improve the behavior of the network is the major challenge is theVariety of intrusion detection mechanisms are being used now a days, to provide security in Wireless Sensor networks (WSN). Since WSN works with set of tiny nodes called as sensor nodes, there are high chances of intrusions for malicious attacks. WSN is deployed in medium open to many users wherever possible. A multiple sensing environment of WSN consists of sensors which acts as agents called as multi agents system for detecting an intruder. Ant colony is an effective approach where each agent communicate with each other for updating the information of intruder to the colony administration. The multi agents based system is best phenomenon suitable for optimization of ant colony. In this approach, the ants form a colony where it goes for search continuously until an intruder is found and once searched, it returns back with the best shortest path available with path traces stored in its database for its future reference. An optimized multi agent approach using ant colony is proposed for detection of lightweight intruders for WSN to protect against harmful malicious attacks. Â Â